GOOD GOVERNANCE THROUGH OFFICIAL DEVELOPMENT ASSISTANCE: ROMANIA’S LEGAL INSTRUMENTS FOR INSTITUTIONAL CONSOLIDATION IN THE REPUBLIC OF MOLDOVA - Copăceanu, Andrei (International Journal of Legal and Social Order, 2025)
The article analyzes the ways in which Romania contributes to strengthening institutional resilience and promoting good governance in the Republic of Moldova through Official Development Assistance (ODA). Based on the legal framework provided by Law no. 213/2016 and key bilateral agreements, the study examines Romania’s role as both donor and strategic partner in supporting democratic reform, legislative harmonization, and administrative capacity building. The analysis draws on RoAid’s Annual Plans and Activity Reports from 2023 and 2024 to identify funding directions, thematic areas, implementation methods, and achieved results. The methodology combines documentary analysis with case study research, focusing on projects aligned with Sustainable Development Goal 16, particularly those targeting the justice system, anti-corruption efforts, and institutional modernization. Romania supports these processes by deploying legal experts, providing technical assistance, and implementing training programs for local public administration, thereby reinforcing the rule of law and judicial independence. Findings reveal a coherent approach grounded in soft power diplomacy and development policy coherence. The Republic of Moldova has received more than half of Romania’s bilateral ODA in recent years, confirming Romania’s role not only as a donor, but also as a model and facilitator of institutional reform. In this context, Romanian ODA emerges as a strategic and normative tool, supporting Moldova’s European integration and contributing to Romania’s commitments under the 2030 Agenda and its OECD accession process.